Effects of a nurse-led family education intervention on the daily living skills of children with autism - Ding, Dandan; Xu, Hiping; Du, Xiaoyan; Su, Xiangdan; Huang, Lijie; Zhang, Xueqin; Hu, Yawen; Wang, Zhaunli; Li, Xuehan; Dai, Jingjing; Zhu, Yiru (Frontiers in Psychiatry, 2025)
BackgroundPatients with autism spectrum disorders have different degrees of daily living skills defects, which can negatively impact their ability to integrate into society. However, the provisioning of nurse-led family education interventions is often not prioritized, and whether family interventions for the parents of children with autism can impact the daily living skills of those children remains poorly understood.ObjectiveTo investigate the effects of a nurse-led family education intervention on the daily living skills of children with autism.MethodsConvenience sampling was used to select children with autism who were hospitalized in the Department of Child Development and Behaviour at a tertiary grade hospital in Zhengzhou, Henan Province, during the period from June 2024 to March 2025. To avoid cross-group contamination, hospitalized patients in the second ward of the Department of Child Developmental Behaviour were used as the intervention group, and hospitalized patients in the first ward of the Department of Child Developmental Behaviour were used as the control group. Researchers collected data before, directly after, and 3 months after the intervention using unified guiding language.ResultsCompared with those before the intervention, directly after intervention and those 3 months after the intervention, the Barthel Index (BI) and Instrumental Activities of Daily Living Scale (IADL) scores for the intervention group significantly increased, whereas the ABC score for that group significantly decreased (P < 0.05). Compared with those of the control group, the intervention group had significantly higher BI and IADL scores and significantly lower ABC scores (P < 0.05).ConclusionsNurse-led family education interventions can improve the daily living skills of children with autism, improve their behavioural characteristics, and promote their effective integration into social life.